Aspects of a critical concept of aesthetical aura (ALPHA. Journal of Arts, Literature and Philosophy, 2019)
The reflections of Critical Theory of society about the modern differentiation of reason, assign to art –and its experience– a singularity which presents itself as a mode of resistance. A paradigmatic moment of this inquiry is the discussion about aura as a key concept to give account of what artistic difference means. In this paper we propose to reconstruct a critical concept of aesthetical aura by means of an interpretation of its place and meaning in Theodor Adorno’s social theory of art. In order to do that, we revise the controversy with Benjamin around the past character of aura; we distinguish the aspects of the foundation of the concept of artistically aura in terms of aesthetical negativity; and, finally, we extract some conclusions in relation to the theoretical contribution of this concept to the critique of aesthetical ideologies.
Keywords: Aura; Theodor Adorno; aesthetical negativity; ideology